Tea and tea products : chemistry and health-promoting properties / Chi-Tang Ho ...[et al] - Shahidi, Fereidoon, 1951-edited by
This text provides extensive coverage of the chemistry, biology, & health promoting properties of most varieties including black, green, & oolong. It presents comprehensive perspectives on tea components that delve into taste components, flavour chemistry & stability, as well as the molecular biology of polyphenols.